Newly designed, fully covered metal stents for endoscopic ultrasound (EUS)-guided transmural drainage of peripancreatic fluid collections: a prospective randomized study - Lee, Byung Uk; Song, Tae Jun; Lee, Sang Soo; Park, Do Hyun; Seo, Dong-Wan; Lee, Sung-Koo; Kim, Myung-Hwan (Endoscopy, 2014)
Background and study aims: Peripancreatic fluid collections (PFCs) have been adequately drained using multiple plastic stents placed in a single-step endoscopic ultrasound (EUS) procedure. Recent reports have presented the usefulness of metal stents for this procedure; however, there has been no prospective comparative study on their effectiveness and safety. We conducted a prospective randomized study to compare multiple plastic stents with fully covered, self-expanding metal stents (FCSEMSs) for the drainage of PFCs.Patients and methods: Between January 2012 and May 2013, patients with PFCs demonstrated by various modalities were enrolled in our study. Patients were randomly assigned to receive either a FCSEMS or plastic stents for EUS-guided PFC drainage. The procedure time, technical success rate, and adverse event rates of the PFCs were evaluated.Results: 50 patients (41 men) were included and randomly assigned to either the FCSEMS group (n = 25) or the plastic stent group (n = 25). The median procedure time with FCSEMS was significantly shorter than with plastic stents (15.0 min vs. 29.5 min, P < 0.01). The technical success rate was 100 % for both groups. The clinical success rate was 20 out of 23 for FCSEMS and 20 out of 22 for plastic stents (P = 0.97). No adverse events occurred in the FCSEMS group, while adverse events occurred in two patients in the plastic stent group (P = 0.16). One recurrence was observed during follow-up in the FCSEMS group and none in the plastic stent group (P = 0.15).Conclusions: EUS-guided PFC drainage with FCSEMSs is comparable to such drainage with plastic stents in terms of technical feasibility, efficacy, and safety; however, the use of FCSEMSs may also simplify and shorten the procedure.Clinical trial registration: KCT0000766 (https://cris.nih.go.kr)